Sosialiasi Teman Tanpa Intimidasi, Say No To Bullying di SD Inpres Kampus Unhas Makassar - Syarif, Kurnia Ali; Manda, Darman; Seppa, Yusi Irensi; Darmayanti, Dyan Paramitha; Arifin, Iqbal (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This community service activity aims to increase awareness of SD Inpres students at the Unhas Makassar Campus on the dangers of bullying and provide education in preventing it. This activity was carried out on May 22, 2024, involving 60 students and 10 teachers. The activity was carried out in three stages, namely the preparation, implementation, and evaluation stages. In the preparation stage, educational materials, including simulation videos, were prepared with legal speakers who emphasized the legal aspects of bullying. The implementation stage included interactive discussions and questions and answers, as well as simulations to help students understand various forms of bullying. The results of the community service activity showed that the socialization had created a safer atmosphere in schools and fostered students' sense of social responsibility. It is recommended that schools continue this effort with the integration of anti-bullying into the curriculum and support from external parties, such as parents, to strengthen positive values ??at home. With the collaboration of all parties, this socialization is expected to be the basis for the formation of a safe and intimidation-free school culture.